(untitled) (SAARC Journal of Agriculture, 2019)
A Petridish and hydroponic culture experiments were conducted at Crop Physiology Laboratory, Department of Crop Botany and Agriculture Chemistry Laboratory, Bangladesh Agricultural University, Mymensingh during the period from August to October 2011 to investigate the effect of aluminium on morphological characters and growth of wheat seedlings. The experiment comprised of two levels of aluminium concentrations viz., 0 μM (control) and 100 μM and five varieties viz; Kanchan, Shatabdi, Sourav, Bijoy (BARI-23) and Sufi (BARI-22). The experiment was laid out in two factors completely randomized design with three replications. Applications of 100 μM aluminium had a profound influence on hypocotyls and epicotyls length, germination percentages, and rootshoot length, fresh and dry mass production in wheat. Results indicated that germination percentage, hypocotyls and epicotyls length, root and shoot length, leaf length, leaf sheath length, plant height, fresh and dry mass plant were greater in control than aluminium stress conditions. It revealed that wheat seedlings are susceptible to aluminium stress. However, among the varieties, the reduction of dry mass under aluminium stress was minimum in Shatabdi followed by Kanchan showed that Shatabdi was more tolerant to aluminium stress than the other varieties namely Sourav, Bijoy (BARI-23) and Sufi (BARI-22). Sufi and Sourav were more susceptible to aluminium stress. SAARC J. Agri., 17(1): 65-76 (2019)